STUDI PERBANDINGAN HASIL BELAJAR FISIKA SESAAT KELAS PUTRA, KELAS PUTRI, DAN KELAS CAMPURAN PADA MATERI GETARAN DI SMA N 1 KRADENAN KABUPATEN GROBOGAN (UPEJ Unnes Physics Education Journal, 2013)
The aim of this research to know is there any difference in instantaneous learning outcomes of physics between the boys class, girls class, and mixed class and know which is the best class. Type of research is True Experimental research with random to subject design. Subjects were 18 students in boys class, 18 students in girls class, and 18 students in mixed class which formed of class XI IPA SMA N 1 Kradenan Grobogan. The learning method used is practical and discussion. Data was taken using the test, observation , documentation, and questionnaires method then this data was analysed using percent descriptive, variants analysis test, and t-test. The research results show there are differences in instantaneous learning outcomes of physics between the boys class, girls class, and mixed class. The best learning outcomes are gotten mixed class with result 70,10, followed by boys class with result 67,78, and the lowest of girls class with result 66,74.